PENGARUH E-LKPD “SI ELMA” (GRAVITASI ELASTISITAS DAN MAGNET) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SDN BANYUAJUH 2 BANGKALAN - Roudhotul Jannah, Alifia; Dya Qurotul A’yun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of the study is to know the effect of the use of E-LKPD "SI ELMA" to the critical thinking skills of students in solving problems and conclude in elementary school. This research uses quantitative research model. However, this study also uses pre-experimental experimental one group pretest-posttest experiment. The results showed that there was a difference between the average pretest and posttest. The average pretest is 50.08 and posttest is 74.40. The test results for improving critical thinking skills are of 0,000 significance. Based on the criterion it can be concluded Ha accepted there is a significant difference between pretest and postest in improving the critical thinking skills of students in stylish materials, elasticity, magnetic and gravity